From pralines to multinationals: The economic history of Belgian chocolate - Maria Garrone; Hannah Pieters; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
Belgium is associated with high-quality chocolate products and Belgian companies play an important role in cocoa processing. However, in historical perspective the global success and reputation of Belgian chocolate is a relatively recent phenomenon. Especially since the 1980s exports of "Belgian chocolates" have grown exponentially. We document the growth of the sector and discuss its determinants. Today, the very concept of "Belgian chocolate" faces challenges, as successful companies have been taken over by international investors and because its success has led others to imitate. Recently there have been attempts to protect "true" Belgian chocolate.
Keywords: 330; Chocolate; Belgium; Economic History; Internationalization